Effects of age and gender on somatosensory evoked potentials [Somatosensoryel uyandirilmiş potansi̇yeller üzeri̇ne yaş ve ci̇nsi̇yeti̇n etki̇leri̇] - (:unkn) unknown (My University, 1999)
Age, height and gender are physiological factors that effect somatosensory evoked potentials (SEPs). In our study, we performed median nerve antidromic sensory and motor conduction velocities and median SEPs on 96 healthy volunteers, 64 females and 32 males. Their ages were between 20 and 70 (mean age of 40.9±12.8). We grouped the volunteers according to age (20-35, 45-54, and 55-70) and gender. We used Erb's point, the cervical and cortical points according to international 10/20 system to obtain the SEPs recordings. We assessed the N9, N13 and N20 peak latencies and amplitudes and central conduction time (CCT). We investigated the correlation of SEPs with age and gender. As a result, we saw that the age and gender have different effects on SEPs.
Keywords: Age; Gender; Somatosensory evoked potentials